2021
DOI: 10.1186/s40104-020-00525-3
|View full text |Cite
|
Sign up to set email alerts
|

MiR-146a-5p targeting SMAD4 and TRAF6 inhibits adipogenensis through TGF-β and AKT/mTORC1 signal pathways in porcine intramuscular preadipocytes

Abstract: Background Intramuscular fat (IMF) content is a vital parameter for assessing pork quality. Increasing evidence has shown that microRNAs (miRNAs) play an important role in regulating porcine IMF deposition. Here, a novel miRNA implicated in porcine IMF adipogenesis was found, and its effect and regulatory mechanism were further explored with respect to intramuscular preadipocyte proliferation and differentiation. Results By porcine adipose tissue m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 49 publications
(52 reference statements)
2
17
0
Order By: Relevance
“…miR-92a protected pancreatic β cells function by targeting KLF2 in diabetes (Wang et al, 2018). miR-146a inhibited adipogenensis through TGF-β and AKT/mTORC1 signal pathways by targeting SMAD4 and TRAF6 in porcine intramuscular preadipocytes (Zhang et al, 2021). miR-125b-5p could suppresses atherosclerotic plaque formation via inhibiting Map4k4 (Lin et al, 2021).…”
Section: Milk-derived Evs and Metabolic Regulationmentioning
confidence: 99%
“…miR-92a protected pancreatic β cells function by targeting KLF2 in diabetes (Wang et al, 2018). miR-146a inhibited adipogenensis through TGF-β and AKT/mTORC1 signal pathways by targeting SMAD4 and TRAF6 in porcine intramuscular preadipocytes (Zhang et al, 2021). miR-125b-5p could suppresses atherosclerotic plaque formation via inhibiting Map4k4 (Lin et al, 2021).…”
Section: Milk-derived Evs and Metabolic Regulationmentioning
confidence: 99%
“…In contrast to these findings, Zhang et al [ 45 ] found that miR-146a-5p expression first increased and then decreased during porcine intermuscular preadipocyte differentiation. A possible reason for this difference is that in-vivo preadipocyte differentiation is affected by adjacent tissues and multiple hormones.…”
Section: Discussionmentioning
confidence: 88%
“…Recent research has shown that some miRNAs participate in adipocyte differentiation; miR-16-5p and Bat-miR-204 promote it, and miR-125a-5p and miR-23a inhibit it [ 13 16 ]. MiR-146a-5p was found to inhibit the differentiation of intramuscular preadipocytes via Akt/mTORC1 signaling in a porcine model [ 17 ], whereas Francisco et al [ 18 ] observed elevated miR-146a-5p expression in differentiated human adipocytes. This miRNA is known to participate in the pathological processes of multiple metabolism-related diseases and obesity [ 19 24 ], but its role in adipocyte differentiation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Activated Smad2 and Smad3 dimerize and together with Smad4 bind to SBEs in the Iα promoter, thereby initiating germline Iα-Cα transcription, the first step in CSR to IgA ( 62 ). Prompted by luciferase reporter assays showing miR-146a targeting of SMAD4 mRNA 3’UTR ( 63 65 ), we used miRNA-mRNA complementarity prediction tools (TargetScan.org, miRNA.org and miRbase.org) to identify miR-146a-specific target sites in the 3’UTRs of human and mouse Smad2/SMAD2, Smad3/SMAD3 and Smad4/SMAD4 ( Figure 6A ), suggesting a potentially silencing of Smad2, Smad3 and Smad4 by miR-146a in both human and mouse B cells. This implies that the miR-146a expression level, which is high in resting B cells, must be dampened by those stimuli that induce CSR to IgA to free Smad2/SMAD2, Smad3/SMAD3 and Smad4/SMAD4 genes from miR-146a silencing for CSR to IgA to unfold.…”
Section: Resultsmentioning
confidence: 99%